LAND COVER CHANGES STUDY OF UPSTREAM COKROYASAN WATERSHED ON MAXIMUM RETENTION - Hanafi, Fahrudin; Budi Nur Sidiq, Wahid Aksin (Universitas Negeri Semarang, 2017)
This research takes location on upstream of Cokroyasan watershed, especially on Bandung weir catchment on Purworejo and Wonosobo District. Research objective is knowing maximum retention changes which represented by upstream Cokroyasan watershed curve number, related to land cover data series, soil type, rain, and peak flow (Qp). Research data quality controlled with data survey and overland flow data observed. Thus the relationship of particular land cover and watershed responses in generating peak flow can be determined.The land covers determine using multispectral classification of Landsat which detailed with manual interpretation and Google Earth image. Sampling selection defines by stratified random sampling technique of the smallest unit of land form. Effective rain determines by consistency test of rainfall data, frequency analysis, survey data and curve number composites. The effective rainfall generate using SCS model (Soil Conservation Service) which influenced by design rainfall, soil type, texture, and land cover.The results showed that within 15 years, the land cover of Bandung weir catchment change significantly. Especially plantation was reduced by 56% or 40.76 km2 while the settlements increased 412% to 64.20 Km2, and other land cover changes not significant (2% <). The analysis showed the peak flow in the upstream of Cokroyasan watershed changes on different return period. Although the different can only see on a more than two years return period. This means there was an increase of peak flow (discharge), as a result of maximum retention DAS dropped from 16- 18.29 m3/ s.The conclusion of this research indicate that land cover changes that occur within 15 years, influence on Curve Number changes, maximum retention, effective precipitation, and peak flow of upstream Cokroyasan watershed.